Strengthening African health systems through outreach and support and values-driven leadership - Louis S. Jenkins; Klaus B. von Pressentin; Zilla North; Gideon van Tonder (AOSIS, 2021)
Healthcare systems are complex adaptive systems, requiring a change in leadership style, from the traditional model to collaborative, values-driven leadership (VDL). Family physicians are well positioned to facilitate integration and coordination between levels of care, across specialties and within teams, in partnership with local and district management team members. This short report describes a leadership innovation experience in a rural South African district, where a VDL course was introduced in a district health context to build on a strong tradition of relationship-centred outreach and support aimed at creating a learning health system. The authors reflect on the contribution of family physicians to strengthen team-based capacity building, care coordination and a learning culture aimed at quality improvement from the perspectives of the regional and district hospital environments. A values-based leadership style will enable family physicians to strengthen team-relationships and create organisational environments, which support shared learning and quality improvement approaches. Ultimately this approach should lead to improved health systems.